Влияние структуры рынка на формирование стоимости ІТ-компаний - Гнесина, Наталия Виталиевна; Ларка, Николай Иванович; Сударкина, Светлана Петровна (НТУ "ХПИ", 2016)
В статье рассматривается важность ІТ-рынка в современных условиях развития мировой экономики. Определена необходимость стоимостной оценки компаний и их составляющих с учетом специфики этого рода деятельности. Проведено исследование структуры IT-рынка Украины; рассмотрены основные направления деятельности телекоммуникационного программного обеспечения (ТПО), определены ключевые факторы роста платформы предоставления услуг, как базовой среди всего комплекса, рассмотрены особенности и рынок прочих направлений ТПО, дана маркетинговая характеристика этого рынка в целом. Обозначены основные факторы, влияющие на процессы капитализации компаний и, соответственно, на их рыночную стоимость.

The article describes the importance of the IT-market in the current conditions of the global economy. The necessity of valuation of companies and their components, taking into account the specifics of this kind of activity. A study of the structure of IT-market in Ukraine has been taken place; the basic directions of activity of software in the telecommunication branch, which includes 6 components; the key factors of growth services platforms as a base among the whole complex have been identified, the features of the market and other areas of telecommunication industry, given the marketing characteristics of the market as a whole. Outlined the main factors influencing the process of capitalization of companies and, accordingly, at their market value. Among them are – the rate of growth of the company by increasing the number of new customers; expansion and modernization of the range of services; the need for a high and sustainable quality management; dynamics of the main indicators of the final profitability of the company, namely the amount of profit percustomer and the dynamics of this indicator.
Influence of market structure on forming of cost of ІТ-companies
Keywords: IТ-рынок; структура; IТ-компании; конкурентоспособность; оценка стоимости; факторы влияния; процессы капитализации; IT-market; structure; IT-companies; competitive; valuation; influencing factors